Silica-encapsulated nanomagnetic particle as a new recoverable biocatalyst carrier. - Tsang, S; Yu, C; Gao, X; Tam, K (2006)
Enzymes are versatile biocatalysts with major advantages of ultrahigh reaction selectivity and specificity under mild conditions, which currently find increasing applications. However, their applications are often hampered by difficulties in recovery and recycling. As a result, we carried out detailed investigations on the synthesis and characterization of silica-encapsulated iron oxide magnetic nanoparticles of controlled dimension as an enzyme carrier. It is shown that the relatively smaller sized silica-coated magnetic nanoparticle prepared by the microemlusion technique can a carry bulky enzyme, beta-lactamase, via chemical linkages on the silica overlayer without severely blocking the enzymatic active center (which is commonly encountered in conventional solid supports). An activity study by Michalis-Menten kinetics reflects that this new type of immobilization allows enzyme isolation with accessibility as good as free enzyme. The recovery and reusability of the nanoparticle-supported enzyme upon application of magnetic separation are also demonstrated.